Analisis Dan Perancangan Sistem Informasi Pariwisata Berbasis Web Sebagai Panduan Wisatawan Pada Kabupaten Kerinci - Sitindaon, Kornelius; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2020)
At present there is not enough information about tourism objects in Kerinci Regency so that not manytourists and also the public know the potential tourism objects. Therefore, this needs to be overcome byproviding more complete and detailed information using web-based information media. The purpose ofdesigning a web-based information system is that tourists are faster and easier as a tourist guide to touristsites in the Kerinci Regency. The research method used is to collect data through literature studies,interviews, and observations, as well as analyzing software requirements, building a database with the UML(Unified Modeling Language) method and displayed in the form of a prototype design in making web-basedtourism information systems. The results of the design in the form of a web-based tourism information systemis expected to be able to become a medium that can develop Kerinci Regency tourism with the design of thisweb design is expected to have a similar design process to produce works that are better and more completethan existing works.